ANALISIS IMPLEMENTASI UJIAN NASIONAL BERBASIS KOMPUTER DENGAN UJIAN BERBASIS KERTAS DI SMPN 3 INGIN JAYA KABUPATEN ACEH BESAR - Mirna Santi; Andika Prajana (UIN Ar-Raniry, 2018)
Today, information technology and computers are not only used for knowledges, but also can be a evaluation for students. This study describes the implementation of UNBK at SMP 3 Ingin Jaya which includes: (1) knowing the internal and external of the student readiness, (2) and knowing about the school readiness. The object of this study is the UNBK activities carried out at SMP 3 Ingin Jaya. The subjects of this study were included 53 students and 2 teachers. This study used the mixed/combination methodologies of the methods. The main data of this study taken from the questionnaires as the quantitative data. Then, to corrected the data of questionnaires, was carried out using qualitative methods, includes observation and interview techniques. The results of this study are the students were ready to UNBK, this was evidenced by the results of obtaining a test score of 83.14% in the questionnaires for UNBK assessment. As for the paper-based national examination assessment questionnaires, the test score was 78%. and schools are ready to implement UNBK without obstacles. But it still has to make improvements to get better results.